The last one if I'm not mistaking
Answer:
sorry I'm not that good at math either it's complicated
Step-by-step explanation:
5
3
(
4
3
⋅
2x^2 + 4x + 1 = 0
2x^2 + 4x + 1 - 1 = 0 - 1
2x^2 + 4x = -1
X(2x + 4) = -1
X = -1.
2x + 4 = -1
2x + 4 - 4 = -1 - 4
2x = -5
2x/2 = -5/2
X = -5/2.
I believe these are the solutions. If not you can use the quadratic formula to solve for the roots, solutions.
It’s not my answer but I think it’s correct!
6 divided by 4(3/5)
After multiplying the fraction we get 23/5
Dividing a fraction will result to multiplying
6 * 23/5
138/5 is the answer.